THE INFLUENCE OF WORK CULTURE ON EMPLOYEE WORK MOTIVATION AT PT. HADJI KALLA (HOLDING) MAKASSAR - Alwiwikh, Moh. Alief Rezkiyah Putra; Anwar, Anwar; Kurniawan, Agung Widhi (Jurnal Manajemen, 2026)
Abstract: This study investigates the influence of work culture on employee work motivation at PT. Hadji Kalla (Holding) Makassar. Employee motivation is widely recognized as a critical factor for organizational performance and long-term sustainability, yet many organizations continue to face challenges in maintaining high levels of motivation among their workforce. At PT. Hadji Kalla, where corporate values and employee development are central, it becomes essential to understand how work culture directly shapes employee motivation. The research employed a quantitative explanatory design aimed at identifying and analyzing the causal relationship between work culture and work motivation. The population consisted of 207 employees, and the study involved 109 respondents who completed structured questionnaires. In addition to the survey, supporting data were collected through observation, interviews, and documentation to enhance reliability. Data analysis was conducted using simple linear regression with the assistance of SPSS version 26, allowing for an objective examination of the extent to which work culture influences employee motivation. The findings reveal that work culture has a significant and positive effect on employee work motivation. Respondents provided a very strong assessment of the existing organizational culture, particularly regarding the internalization of corporate values that shape and guide their work behavior. The study further shows that when employees perceive a strong and consistent work culture, their motivation to perform increases significantly. These results highlight the importance of fostering and maintaining a supportive organizational culture, as it directly enhances employee motivation and contributes to the achievement of organizational goals at PT. Hadji Kalla (Holding) Makassar.Keywords: Celebrity Endorsement, Brand Awareness, Purchase Intention, Scarlett Whitening, Makassar.